The effect of the ethanol extract from the Dracontium spruceanum rhizome on hematologic and biochemical profiles and performance parameters of broiler chickens - Paredes-López, Daniel (2018)
The objective of the research was to evaluate the antioxidant capacity and effect of the ethanol extract from the Dracontium spruceanum rhizome (EERDs) on the blood, biochemical and productive parameters of chickens. To do so, ninety, male, Cobb 500 broiler chickens were used. Once the dehydrated extract was obtained, it was place in the drinking water at concentrations of 0.0, 0.35 and 0.70 mg/mL of EERDs. The birds were distributed into three treatments, five repetitions and each repetition had six chickens. The variance analysis was done with the statistical program InfoStat and the averages of the treatments were analyzed with the 5% Tukey test. The results showed that chickens that consumed drinking water with EERDs presented (p < 0.05) greater concentrations of hematocrit, hemoglobin and erythrocytes; meanwhile, the serum protein and the glucose did not change (p > 0.05). The daily food consumption diminished (p < 0.05) and the DWG and FRC were not influenced (p > 0.05) by the consumption of EERDs in the drinking water. It is concluded that the consumption of EERDs by broiler chickens from 1 to 35 days of age produces greater concentrations of the levels of red blood cells and diminishes the feed intake.